2016
DOI: 10.1080/15487768.2015.1125401
|View full text |Cite
|
Sign up to set email alerts
|

Family-directed cognitive adaptation pilot: Teaching cognitive adaptation to families of individuals with schizophrenia

Abstract: Cognitive deficits are a major determinant of functional outcome in schizophrenia. A promising treatment involves teaching individuals to use cognitive adaptation strategies to minimize the functional impact of cognitive difficulties. We developed Family Directed Cognitive Adaptation (FCA) to train caregivers to help their relatives with schizophrenia use cognitive adaptations to improve living skills. The goal of this open pilot trial was to examine the feasibility of FCA. Ten adults with schizophrenia, each … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 26 publications
1
13
0
Order By: Relevance
“…Among the very few family intervention programs we can mention the Family-Directed Cognitive Adaptation (FCA). This program is designed to teach patients and family members the neurocognitive problems associated with schizophrenia; how to develop compensation strategies to minimize their impact on family and daily functioning; and teach families how to implement adaptive strategies to solve problems [144,145].…”
Section: Some Considerations From Interventions From the Familymentioning
confidence: 99%
See 2 more Smart Citations
“…Among the very few family intervention programs we can mention the Family-Directed Cognitive Adaptation (FCA). This program is designed to teach patients and family members the neurocognitive problems associated with schizophrenia; how to develop compensation strategies to minimize their impact on family and daily functioning; and teach families how to implement adaptive strategies to solve problems [144,145].…”
Section: Some Considerations From Interventions From the Familymentioning
confidence: 99%
“…In a second pilot application of the program to a larger sample [145], the aspects considered most useful by relatives were: "Learning about cognitive deficits related to schizophrenia" and "learning about the specific cognitive strengths and difficulties of my relative" and patients considered: "Learning about my strengths and cognitive difficulties"and "learning strategies to overcome cognitive difficulties". This pilot study suggests that it may have helped family members to better understand the nature of cognitive challenges, which may have reduced feelings of irritation or guilt and with them the family burden.…”
Section: Some Considerations From Interventions From the Familymentioning
confidence: 99%
See 1 more Smart Citation
“…The manual guides the family and their loved one to build SMART (Speci c, Measurable, Achievable, Realistic, and Timely) goals and to use compensatory tools to counter functional di culties associated the disease encountered in daily living. Two small randomized studies showed improvements in community functioning and a signi cant decline of the caregiver-burden [2,27]. Consequently, these preliminary results indicate that raising families' awareness of the compensatory approach could reduce the caregiver's burden and reduce their loved one's di culties with minimal professional help.…”
mentioning
confidence: 95%
“…To overcome these limitations, two groups of researchers [2,27] developed CAT for family, a manualized intervention who helps families throughout all different steps for achieving their relative's goals [27]. The manual guides the family and their loved one to build SMART (Speci c, Measurable, Achievable, Realistic, and Timely) goals and to use compensatory tools to counter functional di culties associated the disease encountered in daily living.…”
mentioning
confidence: 99%